1999
DOI: 10.1117/1.429901
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Reproducibility of Measurements of Human Corneal Thickness with Rapid Optical Low-Coherence Reflectometry (OLCR)

Abstract: This study investigates the precision and intraindividual variability of a clinical optical pachometer based on low-coherence reflectometry, which was used to measure the central thickness of a human cornea in vivo. The instrument, attached to a slit lamp, is a single mode fiber optic based Michelson interferometer with a high repetition rate as previously described. The same operator performed ten sets of measurements on the same subject, each consisting of 20 consecutive scans, on each day for three consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This study is a new application of clinical confocal microscopy to PRK patients. Although the corneal thickness was measured to a precision of approximately 20 microns, which is comparable with ultrasound, it should be pointed out that the new technique of optical low coherence reflectrometry routinely measures the corneal thickness with submicron precision (79,80).…”
Section: Corneal Alterations Following Photorefractive Keratectomy (Prk)mentioning
confidence: 99%
“…This study is a new application of clinical confocal microscopy to PRK patients. Although the corneal thickness was measured to a precision of approximately 20 microns, which is comparable with ultrasound, it should be pointed out that the new technique of optical low coherence reflectrometry routinely measures the corneal thickness with submicron precision (79,80).…”
Section: Corneal Alterations Following Photorefractive Keratectomy (Prk)mentioning
confidence: 99%
“…The measurements of one subject were completed within 30 mins. The average intersession precision (SD) for five subjects was 1.0 mm corresponding with (Bo¨hnke et al 1999). High and low CCT values were determined with the same SD.…”
Section: Equipmentmentioning
confidence: 99%
“…(Bo¨hnke et al (1999) reported a precision of about 1 mm (SD), an intrasession reproducibility around 0.9-1.2 mm and a high intersession reproducibility. Other studies have compared the OLCR pachymeter with the ultrasound pachymeter.…”
Section: Introductionmentioning
confidence: 99%
“…Central corneal thickness is routinely used to monitor corneal edema and endothelial function [26][27][28][29], manage ocular hypertension [30,31], and plan common keratorefractive surgeries such as laser in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK). Ultrasound pachymetry [32,33] and several other techniques [34][35][36][37] provide only spot measurements, while scanning-slit optical pachymetry [38,39], very high-frequency ultrasound imaging [40,41], and optical coherence tomography allow mapping of a wide area of the cornea. Pachymetric mapping provides several advantages over spot measurements.…”
Section: Mapping Of Corneal Thicknessmentioning
confidence: 99%